2023
DOI: 10.3389/fpls.2023.1130724
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic differences between flowers and leaves are driven primarily by pressure-volume traits and water loss

Abstract: Flowers are critical for successful reproduction and have been a major axis of diversification among angiosperms. As the frequency and severity of droughts are increasing globally, maintaining water balance of flowers is crucial for food security and other ecosystem services that rely on flowering. Yet remarkably little is known about the hydraulic strategies of flowers. We characterized hydraulic strategies of leaves and flowers of ten species by combining anatomical observations using light and scanning elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 96 publications
0
9
0
Order By: Relevance
“…After rehydration, the water potential of flowers ( Ψ flower ) and leaves ( Ψ leaf ) and their respective mass were repeatedly measured as they dehydrated on the bench. Before each water potential measurement, samples were enclosed in humidified plastic bags for about 30 min to allow equilibration (An et al, 2023; Rodriguez‐Dominguez et al, 2018). After the measurements, flowers and leaves of each species were oven‐dried at 70°C for 48 h to obtain their dry mass.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After rehydration, the water potential of flowers ( Ψ flower ) and leaves ( Ψ leaf ) and their respective mass were repeatedly measured as they dehydrated on the bench. Before each water potential measurement, samples were enclosed in humidified plastic bags for about 30 min to allow equilibration (An et al, 2023; Rodriguez‐Dominguez et al, 2018). After the measurements, flowers and leaves of each species were oven‐dried at 70°C for 48 h to obtain their dry mass.…”
Section: Methodsmentioning
confidence: 99%
“…As an advantage, the build of this hydrostatic skeleton would probably require a lower carbon investment [e.g., lower values of tissue mass area (TMA) and tissue dry matter content (TDMC)] in an organ that, when compared to leaves, usually has a much shorter lifespan (Roddy et al, 2021). However, although the comparative analysis of the differential carbon and water allocation between organs may provide important insights into key aspects of flower physiology, few studies to date have focused on such comparative analysis (An et al, 2023; Bourbia et al, 2020; Liu et al, 2017; Roddy et al, 2013; Roddy et al, 2019; Roddy, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that extant basal angiosperm lineages require large amounts of water to maintain flower functioning (Feild et al 2009a,b;Roddy et al 2016Roddy et al , 2018. In contrast, in monocots and eudicots, flowers probably rely on stored water to maintain turgidity and delay desiccation (Feild et al 2009b;Roddy et al 2016Roddy et al , 2019Roddy et al , 2023An et al 2023). There is limited information on the diversity of floral hydraulic structure and function in basal angiosperms and their derived clades, specifically in relation to anatomy of the pedicel xylem.…”
Section: Introductionmentioning
confidence: 99%
“…However, under drought conditions, leaf stomata close to limit water loss, causing any remaining water vapor flux to be due to the minimum epidermal surface conductance (g min ), which is due to the conductance of the cuticle and any incompletely closed stomata (Kerstiens, 1996;Duursma et al, 2019;Márquez et al, 2022). After drought-induced stomatal closure in leaves, water loss from flowers can be as high as or even exceed water loss from leaves (Sinha et al, 2022;An et al, 2023), suggesting that corolla g min may hinder the ability of plants to maintain floral display during periods of water stress (Lambrecht, 2013;Buschhaus et al, 2015;Bourbia et al, 2020). Yet, despite the influence of g min on flower and whole-plant hydration and its role in regulating flower temperature, g min has been measured on flowers of only a few species (Patiño & Grace, 2002;Roddy et al, 2016;Roddy, 2019;Bourbia et al, 2020).…”
mentioning
confidence: 99%
“…Here, we compared flowers and leaves in a set of physiological traits that influence water balance, particularly during drought (Brodribb et al, 2007;Boyce et al, 2009;Simonin et al, 2013;Roddy et al, 2016Roddy et al, , 2018Duursma et al, 2019;Bourbia et al, 2020;An et al, 2023). We measured g min , water content per unit projected surface area (W area ) and dry mass (W mass ), vein density (D v ), and dry mass per area (leaf mass per area, LMA, or petal mass per area, PMA) of flowers and leaves for over 100 species from 41 angiosperm families growing in a common garden to determine how these physiological traits differ among organs and influence the costs of floral construction and maintenance.…”
mentioning
confidence: 99%